. Arachis genetic resources: evaluation of peanut smut resistance in wild species: - Rosso, Melina Hebelen; Giordano, Damián Francisco; Oddino, Claudio Marcelo; García, Alejandra Vanina; Soave, Sara Josefina; Soave, Juan; Lavia, Graciela Ines (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Genetic resources are essential for crop improvement. Particularly, wild species related to peanuts are an important source of resistance to various factors. Thecaphora frezii, a pathogen causing peanut smut, leads to yield losses in Argentina’s peanut sector up to 35%. This study evaluated the response of 11 diploid species with A, B, F and K genomes, A. monticola (AABB), and diploid interspecific hybrids (BB), to T. frezii over two cropping seasons. Plants were grown in 20L pots (three replicates each) under field conditions and inoculated with teliospores of the pathogen (20,000 tel./g of soil). The disease was quantified through incidence (% of diseased pods) and severity (scale from 0 to 4). Among A genome species, A. duranensis exhibited the highest incidence at 15.27%; for K genome species, A. batizocoi reached 13.18%. Resistance to T. frezii was observed in the wild species A. diogoi and A. stenosperma (A genome), A. williamsii (B genome), A. trinitensis (F genome), A. cruziana (K genome), and the intragenomic hybrids, constituting new records. Our findings expand the peanut gene pool information for breeders and identify resistant genotypes, supporting the need to preserve wild peanut germplasm to ensure its availability. Highlights: Arachis species with B and F genomes displayed resistance to peanut smut, while AA and KK genome species exhibited varying susceptibility. Genotypes resistant to Tecaphora frezii were identified, expanding the peanut gene pool available for developing resistant genotypes. Wild Arachis species constitute important sources of alleles to diversify A. hypogaea genome and enhance resistance to multiple diseases, including peanut smut. Careful conservation of wild groundnut germplasm is crucial to ensure its availability for future breeding efforts.